An Exploratory Study of Roblox Games as a Medium for Da’wah and Dissemination Strategies through Social Media - Al Kahfi; Muhammad Yudha Ardiansyah; M Gustar Umam; Canra Krisna Jaya; Fajriani Arnol (Syiar: Jurnal Komunikasi dan Penyiaran Islam, 2025)
The rapid development of digital technology has opened new opportunities for Islamic da’wah, including within online gaming environments, allowing young generations to interact and interpret religious messages virtually. This study aims to understand Islamic da’wah practices on Roblox and how young users perceive and disseminate religious messages. A qualitative case study approach was employed, involving digital observation, content documentation, and interaction analysis among avatars within the Roblox platform. Findings reveal diverse da’wah activities, such as virtual study sessions, worship simulations, and Islam-themed roleplay communities, which are shared on social media, particularly TikTok, generating high engagement through likes, comments, and shares. Immersive in-game interactions combined with cross-platform dissemination effectively extend the reach of da’wah messages. Positive responses from both youth and parents indicate that adapting traditional da’wah to virtual spaces is effective, establishing a game-based da’wah model relevant to the digital cultures of Generations Z and Alpha. In conclusion, integrating Roblox and social media creates a participatory, effective, and culturally relevant da’wah model for today’s digital youth.